قاعدة إذا بطل الخصوص هل يبقى العموم : تأصيلاً وتخريجاً - الحصين، عبدالسلام بن إبراهيم بن محمد (وزارة العدل, 2014)
بين الباحث التالي: - معنى القاعدة يتلخص في العام الثابت ضمنا بسبب الأمر الخاص، هل يرتفع بارتفاع ما ثبت به، أم يبقى بعد ارتفاعه؟ وبين أن الفعل أو القول إذا صدر على وجه خاص، وفقد ركنا من أركانه، أو شرطا من شروطه، أو وجد ما يقتضي بطلانه، وفي ضمنه أمر عام ثبت تبعا له، فإن بطلان هذا الأمر الخاص لا يقتضي بطلان الأمر العام، بل يبقي العام صحيحا يمكن بناء الأحكام عليه. 1- أن ظاهر لفظ القاعدة غير مراد؛ لأن العموم لا يرتفع بارتفاع بعض أفراده باتفاق العلماء. - رأى البحث أن ضابط بقاء العموم وعدم بقائه في أمرين: الأول: أن يكون الباقي عاما، بحيث يمكن الحكم ببقائه بعد زوال الأمر الخاص، فإن كان خاصا فلا يحكم ببقائه. الثاني: إمكانية تصحيح الفعل أو القول بدون وصفه الخاص، فمهما أمكن تصحيح الفعل أو القول، فهو أولى من الحكم ببطلانه، ومتى لم يمكن ذلك، فإن العموم يبطل ببطلان وصفه الخاص الذي ثبت به. - أن موضوع القاعدة فقهي وأصولي، يتخرج عليها فروع فقهية، ومسائل أصولية. - بين البحث خلاف العلماء في القاعدة، وحقيقته، وسببه. - عدد بعضا من القواعد المشابهة لهذه القاعدة وفرق بينها، ومن القواعد المشابهة: 1- ما أوجب أعظم الأمرين بخصوصه، لا يوجب أهونهما بعمومه. 2- تخصيص بعض أفراد العام بحكم، هل يقتضي خروجه من العام؟ - عذب بعضا من المسائل الأصولية المخرجة على القاعدة منها: 1- إذا نسخ الوجوب هل يبقي الجواز؟ 2- إذا نسخ التحريم هل تبقى الكراهة؟ - عدد بعضا من المسائل الفقهية المخرجة على القاعدة منها: 1- هل يستحب الجمع بين خصال الكفارة؟ 2- إذا أحرم بفرض، ففسد، أو خرج منه، فهل ينقلب إلى نفل؟ The author discusses the following topics: The meaning of the maxim is whether the established general rule is invalidated by the elimination of the specific reason or remains valid after the elimination of the specific reason. It also means that if the specific act or statement loses any of its pillars or conditions or if anything requires invalidation of it but it involves a general matter that is established based on it, the invalidity of the specific matter does not invalidate the general matter. Rather, the general matter remains valid and rulings can be based on it. The apparent wording of the rule is not intended because the general matter is not invalidated by the loss of any of its elements according to the unanimous agreement of scholars. The author is of the opinion the validity or invalidity of the general matter is controlled by the following: The remaining elements should remain general so that it can be judged as valid after the elimination of specific matter. If it is specific, it is not judged as valid. Possible validity of the act or statement without its specific description. As long as the act or statement is valid, it is better than judging it invalid. If it is not possi¬ble to do so, the general becomes invalid if its specific description which rendered it valid becomes invalid. The subject of the rule relates to jurisprudence and fundamentals of jurispru-dence from which several juristic topics and fundamental questions can be de-rived. The author explains the difference among scholars on the rule, its reality and reason. The author gives account of some similar rules and the differences among them. The author gives account of some juristic issues derived from the rule including the following: Is it likeable to combine the characteristics of expiation? If one starts an obligatory worship but it becomes invalid or leaves it, does it turn to an optional worship?
Keywords: الفقه الإسلامى -- القواعد الشرعية -- الخصوص -- العموم